Evaluation of the Claim that Islam Frightens People with Eternal Pain - Saruhan, Müfit Selim (Millah: Journal of Religious Studies, 2024)
There are various prejudices in society regarding the Islamic concepts of faith. These prejudices are easily eliminated when faced with true knowledge and basic religious sources. Allegations often represent uninformed judgment. The main goal of this article is to clarify a frequently asked question about Islamic beliefs regarding the afterlife. According to some, this question has recently caused young people to break away from faith. To what extent can we embrace a religion that predicts eternal torment? In this article, we draw attention to these prejudices and encourage readers to investigate the intellectual depth of Islam based on knowledge. Humans have great potential. However, a person can achieve happiness in both the world and the hereafter by revealing the potential given to him from birth through his/her choices and behaviors. A person can reveal his existing talent in the best and most accurate way by reflecting on the meanings of the names of his Lord, who created him, in his life and living in accordance with them. Prejudices regarding Islamic religion’s understanding of the afterlife have come to the fore on social media and books. In this article, we discuss the claim about Islam that "it scares us with eternal torment.” Does Islam really scare people with punishments? Are people attached to Islam out of fear, as claimed? Does the Holy Quran suppress questioning? Or does this encourage it? It is possible to find many pros and consensuses in the history of commentary and theology regarding whether punishment is eternal. While evaluating these views, we must be responsible for ensuring and filtering whether they conform to the spirit and basic goals of the Holy Quran and Hadiths. The fact that the names of forgiving, merciful, and merciful are among the beautiful Names of Allah (Al-Asma Al-Husna), but the names of the one who punishes, the one who is angry, and the one who torments are excluded, should be accepted as evidence that the punishment will not be eternal. Mercy is an ancient attribute that cannot be separated from the essence of Allah.